2008
DOI: 10.3390/molecules14010001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Essential Oil and Leaf Anatomy of Salvia bertolonii Vis. and Salvia pratensis L. (Sect. Plethiosphace, Lamiaceae)

Abstract: The taxonomical relationship between Salvia pratensis and S. bertolonii has been unclear for a long time. Salvia bertolonii has alternatively been considered a synonym, a subspecies, a problematic subspecies and a form of Salvia pratensis. However, both these two species are sometimes used in traditional medicine instead of sage (Salvia officinalis) or as an adulteration for the same drug. In order to confirm the status of S. bertolonii, together with the potential identification characteristics for differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…The quantitative area-percent measurements were based on peak-areas from the GC-MS data. Although, some researchers [28,29] have used cluster analysis to evaluate statistical data, the preliminary studies showed that there was no statistically significant differences between extraction and injections since the material was collected at one time [30,31,32,33]. Therefore, no statistical analysis was applied in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative area-percent measurements were based on peak-areas from the GC-MS data. Although, some researchers [28,29] have used cluster analysis to evaluate statistical data, the preliminary studies showed that there was no statistically significant differences between extraction and injections since the material was collected at one time [30,31,32,33]. Therefore, no statistical analysis was applied in this study.…”
Section: Methodsmentioning
confidence: 99%
“…are very scarce. For instance, only one article was available on the EO composition of S. pratensis : Anačkov et al reported that the sesquiterpenes were dominating compounds in this species (55%), whereas monoterpenes (1.4%) were present in remarkably lower concentrations. E ‐Caryophyllene and caryophyllene oxide were the most abundant constituents in S. pratensis analysed in our study; however these sesquiterpenes are typical EO compounds in many aromatic plants; they were also present in the other studied Salvia spp.…”
Section: Discussionmentioning
confidence: 99%
“…glutinosa , S. austriaca and S. amplexicaulis were studied in Serbia . The composition and antimicrobial activity of S. amplexicaulis EO was reported by Petrović et al ; the reports on the composition of EO from S. glutinosa , S. nemorosa and S. pratensis are also available. Kunduhoglu et al reported antimicrobial and anticholinesterase activities of S. verticillata EO.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that Salvia taxa are used in traditional medicines throughout the world (Anackov et al 2009). The genus has a wide, cosmopolitan distribution and displays a remarkable range of variation (Walker et al 2004).…”
Section: Introductionmentioning
confidence: 99%